Past Climate Variability in South America and Surrounding Regions From the Last Glacial Maximum to the Holocene - Vimeux, Francoise; Sylvestre, Florence; Khodri, Myriam (Developments in Paleoenvironmental Research,, 2009)
This book groups together overviews and original research papers dealing with South American climate variability from the Last Glacial Maximum to the Holocene. The contributions deal with tropical, temperate and high latitudes climate variability in South America and in surrounding regions (including Pacific and Atlantic Oceans and Antarctica). It offers results obtained from both natural climate archives and recent simulations from coupled climate models. The objective is to propose a state of the art about our knowledge of past climate variability in South America. Specifically, this book aims at presenting the whole available observations and at discussing climate mechanisms, specifically the low to high latitude teleconnections on that continent which spreads out from the equator to Patagonia. It is written by an expert group of climate change scientists, and presents an insight into dynamics of the past and provides climate modellers with work of reference for data-model comparison. The book is an advanced but very readable text essential for all students and scientists interested in global environmental change.